A tourist facility with a ban on children playing: The principle of non-discrimination and the statement of the Bulgarian court - Yoncheva, Tanya (Turyzm/Tourism, 2024)
Recently, both in Bulgaria and abroad, it is increasingly common to find accommodation, restaurants and entertainment facilities that advertise and offer a wide range of services. However, these are not intended for general consumers but only those who have reached maturity (excluding minors and the under-aged). According to press publications hotels and restaurants that pre-select their guests based on their age are mainly concentrated on the Bulgarian Black Sea coast and in the mountains or they specialize in spa and balneo procedures. It turns out that consumers find it easier to stay with a pet, albeit at an extra cost, than go on vacation with their teenage children. Such practices adopted by representatives of the tourism industry raise some questions of a moral, ethical and legal nature. The current article traces the development of a specific administrative and judicial proceeding initiated to establish the presence of discrimination against consumers in a tourist facility – a restaurant. An overview of the claims and arguments of the claimant is made as well as an analysis of the reasons and considerations given by the competent administrative and judicial authorities. The author’s opinion on the issue is expressed.